2023
DOI: 10.1161/hypertensionaha.123.21592
|View full text |Cite
|
Sign up to set email alerts
|

Editors’ Commentary on the 2023 ESH Management of Arterial Hypertension Guidelines

Abstract: Clinical practice guidelines are ideally suited to the provision of advice on the prevention, diagnosis, evaluation, and management of high blood pressure (BP). The recently published European Society of Hypertension (ESH) 2023 ESH Guidelines for the management of arterial hypertension is the latest in a long series of high BP clinical practice guidelines. It closely resembles the 2018 European Society of Cardiology/ESH guidelines, with incremental rather than major changes. Although the ESH guidelines are pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
5
0
3
Order By: Relevance
“…Fatty liver diagnosis was ultrasound-based ( 30 ). Hypertension was identified through blood pressure measurements, following established criteria ( 31 ). The eGFR calculation employed the Andrew S. Levey formula ( 32 ), with diabetic nephropathy confirmed per KDIGO guidelines when urinary ACR ≥ 30 mg/mmol or eGFR < 60 mL/min/1.73m^ 2 ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fatty liver diagnosis was ultrasound-based ( 30 ). Hypertension was identified through blood pressure measurements, following established criteria ( 31 ). The eGFR calculation employed the Andrew S. Levey formula ( 32 ), with diabetic nephropathy confirmed per KDIGO guidelines when urinary ACR ≥ 30 mg/mmol or eGFR < 60 mL/min/1.73m^ 2 ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, while efficacy clinical trials have consistently shown the ability to produce significant drops in blood pressure, post-trial monitoring indicated that these differences gradually decreased until there was no longer any difference in SBP approximately 5 to 6 years after the trial’s termination, suggesting that the current model of care is not producing satisfactory rates of hypertension control anywhere in the world. The more intensively treated arms in the ACCORD (Action to Control Cardiovascular Risk in Diabetes) and SPRINT (Systolic Blood Pressure Intervention Trial) trials achieved sustained SBP reductions of 14.2 and 16.2 mm Hg, respectively, compared with the standard care arms after treatment titration [ 86 , 87 , 88 ].…”
Section: Current Guidelines For the Management Of Hypertension And Dy...mentioning
confidence: 99%
“…Better blood pressure control for adults with uncomplicated hypertension appears to have been achieved in implementation trials and routine practice settings when using the 2023 ESH Management of Arterial Hypertension Guidelines, which recommend a model that includes elements of accurate and precise blood pressure measurement; health promotion; easy access to a knowledgeable, community-based, patient-centered healthcare team; and the use of simple, evidence-based protocols for lifestyle counseling and antihypertensive drug treatment. Reliability in accessing effective and affordable antihypertensive medications is also recommended, with a preference for the use of single-pill combinations for combination drug therapies [ 22 , 88 ].…”
Section: Current Guidelines For the Management Of Hypertension And Dy...mentioning
confidence: 99%
“…providers, and the community [101][102][103]. More studies are needed to evaluate the factors that lead to a lower prevalence of hypertension at altitude, such as length of residence, ethnic origin, in other countries, and other particular characteristics of these populations, such as environmental and lifestyle factors [104].…”
Section: Plos Onementioning
confidence: 99%